Sistem Pendukung Keputusan Pemilihan Dosen Berprestasi Menggunakan Metode SMARTER Pada Universitas Budi Darma - Natalia Silalahi (Bulletin of Information Technology (BIT), 2020)
Lecturers are one aspect that is involved in the education process at tertiary institutions, where lecturers are part of the academic staff who run the Tri Dharma of Higher Education. At the Tri Dharma College, lecturers are asked not only to conduct education but also carry out research, community service and scientific development. In addition to teaching lecturers as well as forming a good image for a college so that it is necessary to be given an appreciation for the results that have been done by the lecturer. The award is given to increase motivation for lecturers to continue to compete in carrying out the Tri Dharma of Higher Education. Decision support system is an appropriate system used to select outstanding lecturers at Budi Darma University. By using a decision support system, it is possible to get a valid benchmark for the Head of the University of Budi Darma. In this research, the selection of outstanding lecturers was conducted using the SMARTER method, where in the SMARTER the weighting of the criteria and sub-criteria was carried out using the ROC method